Desenvolvimento de um dinamômetro para análise do motor Baja. - Bezerra, Jean Carlos Lima (Universidade Federal Rural do Semi-Árido, 2020)
Dynamometers are the instruments used to use or check the torque of an engine under different operating conditions. These measurements can be performed using various types of dynamometers. Among them or hydraulic, magnetic brake, friction, ventilation, electric and eddy currents. Where in this work there will be greater emphasis on magnetic, hydraulic and eddy current brakes. However, one of the most used in this practice are the hydraulic ones, because they are simpler, lower and easier to build and because there is no need for alignment between the mechanisms, as they are used in magnetic brake dynamometers. With a great growth in the automotive area, the dynamometer became one of the most necessary equipment in the field of mechanical engineering, as it is able to optimize the fuel, fuel and gas intake processes that were used during the burning, during the burning tests use with that instrument. With this, engineers can perform practical tests to use additives in the fuel or mechanisms that allow or not a variation in the engine torque, thus being able to obtain a more powerful engine using simple additive changes or other types of oil. This is no different for BAJA teams looking to build or perfect their bajas, as the dynamometer is capable of checking different types of oil and different characteristics or even the angle of the engine. There is a better way to use it, enabling a car with better characteristics. , with a simple change of factors like oil or angulation. And these changes can be noticed through the use of the dynamometer. With the studies during this work, it will be possible to build a dynamometer capable of measuring the power of the engine, so that it is possible to perform these tests on any engine.
Keywords: Dinamômetro; Torque; Potência; Motor; Engenharia; ENGENHARIAS::ENGENHARIA MECANICA